Perbandingan Kualitas Butir Soal Mata Pelajaran Biologi Berdasarkan Wilayah di Kabupaten Bone Sulawesi Selatan - Oktobianti, Andi Anisa; Adnan, Adnan; Palennari, Muhiddin (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Item quality analysis is one of the important ways to determine the quality of a test. This study aims to determine the comparison of the quality of biology items based on the region in Bone Regency which includes aspects of material, construction, and language. The method used in this research is a survey method with a qualitative descriptive approach. The sampling technique used was cluster sampling, so that 5 schools in Bone district were obtained which represented each region in Bone district and then used purposive sampling technique to select only schools that used multiple choice questions in the end-of-semester test. The results showed that the quality of the items from the material aspect showed that very good items were mostly found in the SMA 5 Bone test questions with a percentage of (86.85%), very good construction aspect items were mostly found in the SMA 5 Bone test questions with a percentage of (98.84%), and very good language aspect items were mostly found in the SMA 14 Bone test questions with a percentage of (96.4%).